2015
DOI: 10.1177/0148607115587947
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Evidence‐Based Nutrition Support Practice Among Healthcare Professionals With and Without the Certified Nutrition Support Clinician Credential

Abstract: Professionals with the CNSC credential scored significantly higher on a complex case-based knowledge assessment of guideline recommendations for the nutrition support treatment of pancreatitis compared with those without a credential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…More than half of the respondents were board certified by NBNSC, and the results indicated that those holding the certification were significantly more likely to choose correct answers compared to those without the credential. Although a certification examination cannot guarantee patient safety, it can help ensure patient safety by identifying those individuals who can demonstrate knowledge through a standardized validated board certification process 15 Question 12.6.…”
Section: Section 12 Documentation and Quality Review Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the respondents were board certified by NBNSC, and the results indicated that those holding the certification were significantly more likely to choose correct answers compared to those without the credential. Although a certification examination cannot guarantee patient safety, it can help ensure patient safety by identifying those individuals who can demonstrate knowledge through a standardized validated board certification process 15 Question 12.6.…”
Section: Section 12 Documentation and Quality Review Issuesmentioning
confidence: 99%
“…Surveys of nutrition support professionals indicate that board certification is critical to providing safe and effective care to patients 14 . Brody and colleagues 15 conducted a survey of healthcare professionals affiliated with ASPEN and used a case‐based scenario based on established clinical guidelines to evaluate knowledge of nutrition support practices. More than half of the respondents were board certified by NBNSC, and the results indicated that those holding the certification were significantly more likely to choose correct answers compared to those without the credential.…”
Section: Section 12 Documentation and Quality Review Issuesmentioning
confidence: 99%
“…This month's issue of the Journal of Parenteral and Enteral Nutrition contains an article by Brody and colleagues 1 entitled, “Evaluating Evidence‐Based Nutrition Support Practice Among Healthcare Professionals With and Without the Certified Nutrition Support Clinician Credential.” In this article, the authors report the results of a study in which they surveyed a sample of convenience of American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) members, asking nutrition support questions about a clinical scenario concerning acute pancreatitis.…”
mentioning
confidence: 99%
“…The Brody et al 1 article highlights some of the challenges facing the nutrition support professional community. It exposes some of the frustrations we have as nutrition support practitioners as we try to demonstrate the value of nutrition support and our value added as nutrition support experts.…”
mentioning
confidence: 99%
See 1 more Smart Citation